Answer:
<h2><u>0</u></h2>
Step-by-step explanation:
If 2u-6=4, let's solve for u.
Add 6 to both sides
2u-6+6 = 4+6
Simplify
2u = 10
Divide both sides by 2
u = 5
Now, we can solve u-5
5-5 = 0
Answer:
y = 2(x-3)^2 - 2
Step-by-step explanation:
y = 2x^2 - 12x + 16
y = 2(x^2 - 6x + 8)
y = 2(x^2 - 6x +8 +1 -1) you "complete the square" by bringing the last term (8) up to "half of the middle co-efficient squared". Middle co-efficient is -6, half is -3, squared is 9. To get from 8 to 9 you must add 1 (+1), but if you add 1 you must subtract 1 (-1) so that you don't change the overall value of inside the bracket
y = 2(x^2 - 6x +9) - 2 (bring the -1 outside of the brackets)
y = 2(x-3)^2 - 2
Answer:
Jamyra spent 23 minutes studying last week.
Step-by-step explanation:
100 - 8 = 92
92 ÷ 4 = 23.
Answer:
$55.80
Step-by-step explanation:
8, 16, 24, 32, 36
8=12.40, 16=24.80, 24=37.2, 32=49.6,
+4 makes it 36 so it's have of 8, so add 6.20 to the end and it's 55.80
N equals 1.125. Percent are y’all going to be doing okay now lol ima is my life day to wiwiwiwiwiwiwow